Dialysate sodium prescription and blood pressure in hemodialysis patients - Hecking, Manfred; Karaboyas, Angelo; Rayner, Hugh; Saran, Rajiv; Sen, Ananda; Inaba, Masaaki; Bommer, Jürgen; Hörl, Walter H.; Pisoni, Ronald L.; Robinson, Bruce M.; Sunder-Plassmann, Gere; Port, Friedrich K. (American journal of hypertension, 2014)
BACKGROUND. Diffusive sodium removal has been recommended to control hypertension in hemodialysis patients. Recent evidence on hospitalizations and mortality,
Gesehen am 04.09.2020